Pencapaian Sustainable Development Goals di Sumatera Barat melalui Pertanian Berkelanjutan - Dina Yulianti; Arry Bainus; Virtuous Setyaka; Deasy Silvya Sari; Alyandani Ayu Kinanti (Andalas Institute of International Studies UNAND, 2024)
Sustainable Development Goals (SDGs) are a set of international agreements on efforts that must be made to create a just, prosperous, and safe world for humans and the planet Earth. Efforts to achieve SDG number 2, namely